2016
DOI: 10.1160/th15-06-0477
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is associated with high levels of monocyte-platelet-aggregates and increased CD11b expression in patients with aortic stenosis

Abstract: A growing body of evidence suggests a pivotal role of inflammatory processes in AF in a bidirectional manner. Infiltrating leukocytes seem to promote both structural and electrical remodelling processes in patients with AF. Monocyte-platelets-aggregates (MPAs) are sensitive markers of both platelets and monocyte activation. So far it is not clear whether the content of MPAs is affected by AF. The present study examined the content of MPAs and the activation of monocytes in elderly patients with an aortic steno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We concluded that the protective effects of LIF occur during early period following stroke. It is known that various immune cells contribute to inflammation and that these cells can express inflammation-related proteins on their surface or release inflammation-related factors to their extracellular environments [ 24 , 25 ]. Pro-inflammatory genes accelerate the damage of ischemic tissue while anti-inflammation related genes promote the repair of ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that the protective effects of LIF occur during early period following stroke. It is known that various immune cells contribute to inflammation and that these cells can express inflammation-related proteins on their surface or release inflammation-related factors to their extracellular environments [ 24 , 25 ]. Pro-inflammatory genes accelerate the damage of ischemic tissue while anti-inflammation related genes promote the repair of ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…It also permits expression analysis of various platelet activation markers as well as platelet receptors on distinct platelets. Furthermore, flow cytometry allows the quantification analysis of the associates that link platelet to the other blood cells [211215]. …”
Section: Platelets Hyperactivity In T2dmmentioning
confidence: 99%
“…Leukocyte infiltration into tissue can promote collagen breakdown and structural remodeling processes, triggering oxidative stress 41 , leading in turn to ischemic heart failure 42 . Infiltrating leukocytes and PLA seem to promote structural and electrical remodeling in patients with atrial fibrillation 43 , which may also result in heart dysfunction and even failure.…”
Section: Discussionmentioning
confidence: 99%